TRANSLATION APPROACHES IN A MULTILINGUAL AND PLURILEGAL SETTING: CANADA AND THE EU - YANKOVA, Diana (Comparative Legilinguistics, 2009)
Th is paper willfocus on the converging and diverging elements of the idiosyncratic legal regimes of federal Canada and of the supranational European Union. The methodology applied in Canada in terms of the stages in identifying the points of contact between the diff erent legal systems and languages in relation to the procedure adopted in cases of conceptual and terminological non-correspondence, as well as the draft ing techniques employed and the justifi cation for choice in each particular instance, will be highlighted. The Canadian approach to terminological issues in the ongoing process of harmonizing federal legislation will be considered as a possible model for felicitous solutions regarding current pressing diffi culties in the translation of legal terms in the European Union.